Virtual 3rd IRNI symposium 2022: exploring recent advancements in drug discovery and development / Dr. Ravi Sheshala and Dr. Gurmeet Kaur Surindar Singh - Sheshala, Ravi; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
The Virtual 3rd IRNI Symposium 2022, a two-day international scientific event (23-24 November 2022) centred around the theme “Shaping the Future of Medicine: Recent Advancements in Drug Discovery and Development” was organised by the Faculty of Pharmacy, UiTM, with the aim of sharing valuable knowledge and showcasing the latest inventions in drug discovery and development. This programme was conducted in collaboration with MoU partner universities, inviting plenary speakers from Queen’s University Belfast (QUB), United Kingdom; Gandhi Institute of Technology and Management (GITAM) University, India; Institut Teknologi Bandung, Indonesia; Mahidol University, Thailand; Pharmaniaga Berhad, Malaysia’s renowned pharmaceutical industry; and other prestigious universities such as University College London, United Kingdom and University of Sharjah, United Arab Emirates.